Pengaruh Psychological Ownership terhadap Voice Behavior - Delyara, Dea Ayu; Suhariadi, Fendy (FENOMENA, 2020)
This study aims to determine the direct effect of psychological ownership on voice behavior. The research data obtained by 223 respondents and are employees who work at state-owned companies. The sampling technique used in this study was a combination of accidental sampling and snowball sampling. This study uses a psychological ownership scale adapted from Avey (2009) and a voice behavior scale adapted from Liang (2007). Furthermore, data analysis was performed using the Partial Least Square method. The results of this study indicate that there is a positive and significant direct influence between psychological ownership of voice behavior.